2008
DOI: 10.1016/j.prp.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Lung granulomas from Mycobacterium tuberculosis/HIV-1 co-infected patients display decreased in situ TNF production

Abstract: Tuberculosis/HIV-1 co-infection is responsible for thousands of deaths each year, and previous studies have reported that co-infected individuals display major morphological alterations in tissue granulomas. The purpose of this study was to evaluate immunohistopathological characteristics in lung tissues from pulmonary TB/HIV-1-co-infected individuals. Following autopsy, tuberculosis-positive HIV-1-negative cases displayed granulomas with normal architecture, mainly composed of a mononuclear infiltrate with ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
64
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 27 publications
7
64
1
Order By: Relevance
“…Coinfection with HIV and M. tuberculosis is likely to result in dissemination of M. tuberculosis (51). Lung granulomas from M. tuberculosis/ HIV-1-coinfected patients display decreased in situ TNF production (52) Our data revealed that LY6E exerts its role through downregulating CD14 expression at the transcriptional step but not the stage of protein stability or degradation. The possibility remains that the transcriptional machinery involved in CD14 expression, such as the activity of transcription factors and the transcriptional status of the promoter region, may be influenced by the LY6E pathway.…”
Section: Discussionmentioning
confidence: 67%
“…Coinfection with HIV and M. tuberculosis is likely to result in dissemination of M. tuberculosis (51). Lung granulomas from M. tuberculosis/ HIV-1-coinfected patients display decreased in situ TNF production (52) Our data revealed that LY6E exerts its role through downregulating CD14 expression at the transcriptional step but not the stage of protein stability or degradation. The possibility remains that the transcriptional machinery involved in CD14 expression, such as the activity of transcription factors and the transcriptional status of the promoter region, may be influenced by the LY6E pathway.…”
Section: Discussionmentioning
confidence: 67%
“…If the increase in cytokine mRNA leads to increased inflammation, excessive pathology or changes in granuloma function and architecture may occur that inhibit the control of M. tuberculosis infection. Contrary to the previous result, another immunohistochemistry study determined that granulomas from HIV ϩ individuals with TB expressed less TNF and had more extensive necrosis than granulomas from individuals with TB alone (20). The decrease in TNF expression may be due to a functional disruption or a decrease in the number of T cells and infected macrophages within the granulomas.…”
Section: Changes In M Tuberculosis-specific T Cell Responsesmentioning
confidence: 60%
“…tuberculosis coinfection is caused by a functional disruption of the local immune response within the granuloma (3,20,50,83,91). These disruptions presumably decrease the ability of the granuloma to contain M. tuberculosis, leading to increased bacterial growth with more mycobacterial dissemination and severe pathology.…”
Section: Effects Of Hiv On the M Tuberculosis Granulomamentioning
confidence: 99%
“…Despite this, percentages of enumerated granulomas demonstrating caseous necrosis significantly increased after IFN-γ and TNF-α blocking, indicating that granuloma caseation is exacerbated by immune suppression ( Figure 2D). T cells and macrophages are the predominant cell types seen in human granulomas (22), contrasting with neutrophilic infiltrates predominantly seen in granulomatous lesions of Nos2 -/-mice after aerosol infection (21,23). To further qualify our assertion that caseous granulomas observed after dermal infection of Nos2 -/-mice were more representative of human granulomas, we stained lungs of aerosol-infected mice at day 30 p.i.…”
Section: Dermal Infection Of Nos2 -/-Mice Produces a Ghon Complex-likmentioning
confidence: 97%